Multilayer design of crN/MoN superhard protective coatings and their characterisation - Postolnyi, B. O. (2019)
Multilayer CrN/MoN transition metal nitride coatings were studied in this research. Films were deposited by vacuum arc deposition (Arc-PVD) from Cr and Mo cathodes in nitrogen atmosphere p = 0.4 Pa. Three series of samples with different values of negative bias voltage (−20, −150, and −300 V) applied to the surface were fabricated. Each series has samples with 11, 22, 44, 88, 180 and 354 layers while total thickness was maintained with the same value. Samples were studied by scanning electron microscopy (SEM) on cross-sections and coatings surface, energy-dispersive X-ray spectroscopy (EDS), electron backscatter diffraction (EBSD), high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), micro-indentation. Two main cubic phases of γ-Mo N and cubic CrN were detected. It was observed that the crystal growth orientation changes while the negative bias voltage of the substrate decreases. The maximum values of hardness (38–42 GPa) among the studied samples were obtained for coatings with a minimal individual layer thickness of 20 nm deposited at U = −20 V. N 2 b